2019
DOI: 10.1038/s41422-019-0241-9
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Parkinson’s disease from gut to brain by δ-secretase

Abstract: Lewy pathology, composed of α-Synuclein (α-Syn) inclusions, a hallmark of Parkinson's disease (PD), progressively spreads from the enteric nervous system (ENS) to the central nervous system (CNS). However, it remains unclear how this process is regulated at a molecular level. Here we show that δ-secretase (asparagine endopeptidase, AEP) cleaves both α-Syn at N103 and Tau at N368, and mediates their fibrillization and retrograde propagation from the gut to the brain, triggering nigra dopaminergic neuronal loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 55 publications
2
82
0
Order By: Relevance
“…Extending the study of prion-like seeding capacity of truncated αsyn fibrils to cellular and animal models is complicated due to additional extrinsic factors now involved such as modulation of cellular uptake and spread of fibrils due to truncation (194,195), trafficking to subcellular compartments (196), and structural changes to the truncated fibril due to additional PTMs; most of these variables have not been studied in relation to truncated αsyn fibrils or even typical αsyn seeding experiments. Nonetheless, cellular (22, 38, 91-93, 103, 120, 159, 189, 197, 198) and animal (133,159,189,199) experiments using fibrils containing truncated αsyn have shown some similar findings to in vitro studies.…”
Section: Fibrils Containing Truncated αSyn Have Strain-like Variationmentioning
confidence: 79%
See 3 more Smart Citations
“…Extending the study of prion-like seeding capacity of truncated αsyn fibrils to cellular and animal models is complicated due to additional extrinsic factors now involved such as modulation of cellular uptake and spread of fibrils due to truncation (194,195), trafficking to subcellular compartments (196), and structural changes to the truncated fibril due to additional PTMs; most of these variables have not been studied in relation to truncated αsyn fibrils or even typical αsyn seeding experiments. Nonetheless, cellular (22, 38, 91-93, 103, 120, 159, 189, 197, 198) and animal (133,159,189,199) experiments using fibrils containing truncated αsyn have shown some similar findings to in vitro studies.…”
Section: Fibrils Containing Truncated αSyn Have Strain-like Variationmentioning
confidence: 79%
“…Our lab has demonstrated that fibrils containing both C-truncated and FL αsyn in a 1:1 ratio seed similarly to, or slightly less than, FL αsyn fibrils suggesting that the extreme structural alterations of fibrils comprised of C-truncated αsyn are attenuated in this configuration (22,159). Additionally, fibrils comprised of truncated αsyn may interact with other neurodegenerative proteins as well, as a seed containing both 1-103 truncated αsyn and truncated tau was superiorly able to induce αsyn pathology when injected into mice compared with 1-103 or FL αsyn fibrils which were themselves about equal in prion-like potency (133).…”
Section: Fibrils Containing Truncated αSyn Have Strain-like Variationmentioning
confidence: 96%
See 2 more Smart Citations
“…Although we used an immunohistochemical method that has been repeatedly demonstrated to be highly sensitive and specific for both CNS and PNS -synuclein pathology, as found in multi-center blinded studies [69,70,78,88] and biochemical studies [75], it is possible that the initial form of peripheral -synuclein pathology may differ from that commonly seen in the CNS. Alternate forms may include non-phosphorylated -synuclein, truncated -synuclein [89][90][91] and -synuclein aggregates [39,92].…”
Section: Discussionmentioning
confidence: 99%